AC CALORIMETRY AT CDW AND SDW TRANSITIONS - CHUNG, M; WANG, YQ; BRILL, JW; BURGIN, T; MONTGOMERY, LK (ELSEVIER SCIENCE SA LAUSANNE, 1993)
We have measured the specific heat at the SDW transition in kappa-(BEDT-TTF)2Cu[N(CN)2]Cl and the CDW transitions in ZrTe3, blue bronze, and (TMTSF)2ReO4. No anomaly is observed at the SDW transition. For ZrTe3, a small peak, DELTAc(p) approximately 0.065R, is observed. For blue bronze and (TMTSF)2ReO4, the changes in c(p) are 3-4 times their calculated mean-field values, as expected for 1-D systems. For (TMTSF)2ReO4, there is also sample dependent latent heat associated with anion ordering.
Keywords: METAL-INSULATOR-TRANSITION; PEIERLS TRANSITION; ZRTE3; THERMODYNAMICS